Hydroxysafflor yellow A: a natural pigment with potential anticancer therapeutic effect - Wang, Yuhan; An, Junsha; Zhou, Jianbo; Chang, Liming; Zhang, Quan; Peng, Fu (Frontiers in Pharmacology, 2025)
Hydroxysafflor yellow A (HSYA), a natural pigment with a chalcone structure extracted from Carthamus tinctorius L. (Safflower), has been widely proven to have good efficacy on cardiovascular diseases, atherosclerosis, cancer, and diabetes. However, no study has reported on the anticancer mechanisms of Hydroxysafflor yellow A (HSYA), a principal bioactive compound in safflower. This review discusses recent developments in the physicochemical properties and sources, pharmacological effects and mechanisms, pharmacokinetic progress, and safety of HSYA, focusing on the involvement of HSYA in the regulation of related pathways and mechanisms of apoptosis, autophagy, and the tumor immune microenvironment in a variety of cancers. This can serve as a theoretical basis for further research and development of HSYA, with insights into the mechanisms of anticancer signaling pathways.